PERAN GAME EDUKATIF DIGITAL DALAM MENINGKATKAN KREATIVITAS DAN KETERAMPILAN PROBLEM SOLVING SEKOLAH DASAR - Ulfa, Siti Maria; Febriyanti, Alvina Eka; Yulia, Nurul Mahruzah; Fitriana, Ana Fashol; Jenisa, Nur Mala; Sulistyowati (PGMI UNHASY, 2025)
The development of digital technology offers new opportunities in the world of education, especially through the use of digital educational games. The purpose of this study was to examine the role of digital educational games in enhancing creativity and problem solving among elementary school students. The research method used was a quantitative study with a quasi-experimental approach involving 20 grade IV students at Tlogogung State Elementary School. Data were collected by pre-test and post-test, as well as observation of student activities, while using educational games based on problem solving. The results showed that there was a significant increase in aspects of creativity and problem solving skills after students were involved in digital educational games for four weeks. With interactive elements, cognitive challenges and direct feedback, the game can stimulate various thoughts and increase students' confidence in solving problems. This realization shows that digital educational games are not only entertainment tools, but also effective learning tools in developing important skills for children in the 21st century. Recommendations are given to educators and educational technology developers for the design of game content that meets the needs of the curriculum and child development.